THE APPLICATION OF OXYTOCIN MASSAGE IN POST PARTUM MOTHER CARE TO OVERCOME BREASTFEEDING PROBLEMS IS NOT EFFECTIVE IN THE WORK AREA OF PUTRI AYU COMMUNITY HEALTH CENTER JAMBI CITY - Putri Dwita; Mutmainnah, Muthia (Program Studi Keperawatan Fakultas Kedokteran dan Ilmu Kesehatan Universitas Jambi, 2023)
Newborns need to receive optimal care from birth, one of which is ideal food. Mother's Milk (ASI) is the most recommended food for babies at least in the first 6 months of life. But in reality, exclusive breastfeeding is not as easy as imagined. Various obstacles can arise in efforts to provide exclusive breastfeeding for the first six months of a baby's life. Purpose of this study is to provide the application of Oxytocin Massage in the care of post partum mothers to overcome the problem of ineffective breastfeeding in the working area of ​​the Putri Ayu Public Health Center, Jambi City. Method used is a case study with data collection techniques through observation, interviews, and physical examination with superior interventions, namely oxytocin massage to overcome ineffective breastfeeding problems. Result: the analysis showed that there was a diagnosis of Ineffective Breastfeeding by giving Oxytocin Massage for 5 days, it was found that after the intervention there was an increase in milk production in post partum mothers on the first day there were no visible drops of milk coming out but after the intervention on the fourth and fifth days there were drops/ milk emission that comes out during oxytocin massage. It can be concluded that oxytocin massage can increase milk production in post partum mothers.